Hubungan Self Compassion Terhadap Tingkat Stres Akademik Pada Mahasiswa Baru Fakultas Psikologi UNM - Erwansa, Dedi; Widyastuti, Widyastuti; Ridfah, Ahmad (CV. Ulil Albab Corp, 2024)
Students who are less able to adjust to the campus environment can cause stres. Academic stres can hinder achievement and harm students, so they need coping strategies to reduce stres with self-compassion. This study aims to examine the relationship between academic stres and self-compassion in new students of the psychology faculty of UNM. The method used in this study is a correlational quantitative method with a total of 206 new students from the class of 2020. The data analysis technique used in this study is Sprearman Rank Correlation. The results showed that there was a relationship between self-compassion and academic stres (p=0.00 and r=-484). This means that there is a very significant negative relationship between self-compassion and academic stres. The results of this study are expected to be a reference for new students regarding the importance of practicing self-compassion in daily activities.